2009
DOI: 10.1177/0022034508330176
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Peripheral Receptor Targets for Deep-tissue Craniofacial Pain Therapies

Abstract: While effective therapies are available for some types of craniofacial pain, treatments for deeptissue craniofacial pain such as temporomandibular disorders are less efficacious. Several ion channels and receptors which are prominent in craniofacial nociceptive mechanisms have been identified on trigeminal primary afferent neurons. Many of these receptors and channels exhibit unusual distributions compared with extracranial regions. For example, expression of the ATP receptor P2X 3 is strongly implicated in no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
19
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 135 publications
4
19
0
Order By: Relevance
“…Most of these co‐expressing cells were small‐ to medium‐sized neurons. As previously reported, whilst P2X 3 ‐positive neurons in dorsal root ganglia rarely express neuropeptides, extensive co‐expression of P2X 3 and neuropeptides is found in TG neurons, suggesting a far greater interaction between neuropeptides and P2X 3 in craniofacial pain . Recent studies have already demonstrated the stimulating effects of Substance P and CGRP on P2X 3 receptor .…”
Section: Discussionsupporting
confidence: 66%
“…Most of these co‐expressing cells were small‐ to medium‐sized neurons. As previously reported, whilst P2X 3 ‐positive neurons in dorsal root ganglia rarely express neuropeptides, extensive co‐expression of P2X 3 and neuropeptides is found in TG neurons, suggesting a far greater interaction between neuropeptides and P2X 3 in craniofacial pain . Recent studies have already demonstrated the stimulating effects of Substance P and CGRP on P2X 3 receptor .…”
Section: Discussionsupporting
confidence: 66%
“…Although a central origin of migraine attacks has been proposed, it seems likely that the acute onset of headache is at least partly due to sensitization of trigeminal sensory neurons [1][2][3], the large majority of which are activated by extracellular adenosine-5′-triphosphate (ATP) via purinergic ionotropic receptor 3 (P2X3)-sensitive receptors [4][5][6]. Trigeminal ganglion sensory neurons of a transgenic mouse model (i.e., R192Q knockin (KI)) expressing the R192Q missense mutation in the α1 subunit of the P/Q-type Ca 2+ channel that is encoded by the Cacna1a gene [7], and which causes human familial migraine type-1 (FHM-1), show functional upregulation of P2X3 receptors under basal conditions consistent with their constitutive sensitization [8].…”
Section: Introductionmentioning
confidence: 99%
“…Thus muscle damage, subsequent inflammation and increased primary afferent drive could initiate or exacerbate chronic craniofacial pain. A high percentage of craniofacial deep tissue primary afferent neurons also express the P2X 3 receptor and co-localize CGRP with P2X 3 [2]. …”
Section: Introductionmentioning
confidence: 99%